2012
DOI: 10.4103/0974-1208.101023
|View full text |Cite
|
Sign up to set email alerts
|

Anti-mullerian hormone cut-off values for predicting poor ovarian response to exogenous ovarian stimulation in in-vitro fertilization

Abstract: OBJECTIVES:(a) To establish the cut-off levels for anti-Mullerian hormone (AMH) in a population of Indian women that would determine poor response. (b) To determine which among the three ie.,: age, follicle stimulating hormone (FSH), or AMH, is the better determinant of ovarian reserve.STUDY DESIGN:Prospective observational study.SETTING:In vitro fertilization (IVF) unit of a tertiary hospital.MATERIALS AND METHODS:The inclusion criterion was all women who presented to the center for in-vitro fertilization/Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 30 publications
1
36
0
1
Order By: Relevance
“…Regarding treatment, immunosuppressive agents, particularly intravenous cyclophosphamide, may alter menstrual cycles and ovarian reserve in female SLE and juvenile DM [5,17,18,22,23]. However, in the present study, the possible role of treatment in reduced ovarian reserve cannot be completely excluded since all patients had long-term exposure to multiple immunosuppressives and one of them was treated with cyclophosphamide.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Regarding treatment, immunosuppressive agents, particularly intravenous cyclophosphamide, may alter menstrual cycles and ovarian reserve in female SLE and juvenile DM [5,17,18,22,23]. However, in the present study, the possible role of treatment in reduced ovarian reserve cannot be completely excluded since all patients had long-term exposure to multiple immunosuppressives and one of them was treated with cyclophosphamide.…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, as recent studies have reported that decreased AMH levels can be observed in women using hormonal contraceptives [17,18], the ovarian hormonal profile described herein was determined without the effect of any exogenous hormone for a period of at least 6 months to avoid this possible bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding the extensive number of scientific papers in the last few years, no definitive consensus exists on the characterization of altered ovarian function [29]. A combination of hormonal markers like serum follicle-stimulating hormone (FSH) [52], serum AMH [79] and the antral follicle count [77] may help in diagnosing early decline in ovarian follicular activity. The antral follicle count remains perhaps the best predictor of the ovarian response to the controlled ovarian stimulation after the AMH assay itself [80,88] Although early follicular phase serum FSH levels are a well established marker of ovarian reserve [18], the correlation may be poor compared to other markers.…”
Section: Cgg Mutations and Biomarkers Of Ovarian Reservementioning
confidence: 99%
“…Early predictive tests that emphasize the probability of achieving high quality oocytes during ovarian stimulation are needed to decide whether to continue or abandon the current cycle. Although high gonadotropin utilization with longer periods of stimulation achieves fewer and possibly low quality follicles and a lower estradiol increase during ovarian stimulation of these patients adversely impact the success of the assisted reproductive techniques [Satwik et al 2012]. Ovarian response to COH is monitored by serial maternal serum estradiol (E2) level measurements and ultrasonographic surveillance of follicle growth.…”
Section: Introductionmentioning
confidence: 99%